Influence of High Temperature on the Physical and Mechanical Properties of Porous Limestone from Baku (Azerbaijan) - Clara Jodry; Michael J. Heap; Kamal Bayramov; Gunel Alizada; Sona Rustamova; Sevinj Nabiyeva (Fire, 2023)
Limestone is a popular building stone worldwide. In Baku in Azerbaijan, local limestones have been used in construction, including in the walled historic city centre (Old City, Icherisheher). Located in a seismically-active area, Baku is prone to post-earthquake fires that can damage buildings and monuments. Here, we test the fire resistance of local limestone by measuring its physical (connected porosity, permeability, P-wave velocity, thermal properties) and mechanical (uniaxial compressive strength, Young’s modulus) properties before and after thermal-stressing to temperatures up to 600 °C. Our results show that connected porosity and permeability increase and that P-wave velocity, thermal conductivity, thermal diffusivity, specific heat capacity, uniaxial compressive strength, and Young’s modulus decrease as a function of increasing temperature. Microstructural analyses show that these changes are the result of thermal microcracking. Samples heated to 800 °C disintegrated due to the formation of portlandite following decarbonation. The data presented herein will assist damage assessments of limestone buildings and monuments in Baku following the unfortunate event of fire.